(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2025)
Creditworthiness plays a crucial role in the financial management of young people, who are increasingly interested in loans as they strive for financial independence. Despite the growing demand for loans (especially mortgages), many young individuals lack sufficient knowledge about creditworthiness, which can lead to poor financial decisions. Therefore, the primary objective of the study was to assess the level of knowledge among young people regarding creditworthiness and its impact on their financial decisions. A survey was conducted among young people in the Greater Poland Voivodeship to address the following research questions: Do young people understand what creditworthiness is? What are the consequences of having high or low creditworthiness? What financial behaviors influence creditworthiness? Are young people aware of their current creditworthiness, and do they plan to take out a loan in the future? The empirical research revealed that while young people generally have a high level of basic knowledge about creditworthiness, it is incomplete. Older respondents (among the surveyed young individuals up to the age of 29) demonstrate greater financial awareness and practical experience, with real estate loans being the dominant financial goal among young people. There is also insufficient awareness among young people about some of the consequences of low creditworthiness.